2020
DOI: 10.1155/2020/4319398
|View full text |Cite
|
Sign up to set email alerts
|

Tannase‐Converted Green Tea Extract with High (−)‐Epicatechin Inhibits Skeletal Muscle Mass in Aged Mice

Abstract: The objective of this study was to investigate the effects of tannase-converted green tea extract on body composition, muscle oxidative stress-related factors, and differentiation-related factors. The mean bone-related parameters and body composition were determined by the live dual-energy X-ray absorptiometry (DEXA). Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were used to determine mRNA expression and protein levels, respectively. The results of total mass testing in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The results of in vitro experiments showed the beneficial effects of epicatechin on muscle wasting and muscle function. Additionally, epicatechin increased the mRNA expression of MyoD, superoxide dismutase (SOD), and catalase in the biceps femoris muscle and decreased the expression of FoxO3, myostatin, and MuRF1 in the soleus muscle (Hong et al, 2020). Si et al (2019) observed that epicatechin increased the survival rate of aged mice and delayed the degeneration of skeletal muscle.…”
Section: Epicatechinmentioning
confidence: 99%
“…The results of in vitro experiments showed the beneficial effects of epicatechin on muscle wasting and muscle function. Additionally, epicatechin increased the mRNA expression of MyoD, superoxide dismutase (SOD), and catalase in the biceps femoris muscle and decreased the expression of FoxO3, myostatin, and MuRF1 in the soleus muscle (Hong et al, 2020). Si et al (2019) observed that epicatechin increased the survival rate of aged mice and delayed the degeneration of skeletal muscle.…”
Section: Epicatechinmentioning
confidence: 99%
“…The findings that GTE supplementation enhances total antioxidant potential (i.e., GSH-Px, SOD, CAT) and lowers carbonylated protein levels in skeletal muscle are consistent in a variety of rodent models including BALB/c mice, female Sprague-Dawley rats, and male Kunming mice [101][102][103]. Interestingly, in male ICR mice, tannase-converted GTE (80 µM) with greater antioxidant capacity increased antioxidant enzyme SOD and CAT content [104].…”
Section: Rodent Studiesmentioning
confidence: 62%
“…These observations are consistent with previous results from our group showing that EC administration resulted in a significant increase in the expression of muscle differentiation genes, such as myoblast determination protein (MyoD) and myogenin genes in stressed C2C12 muscle cells [20]. The levels of factors related to muscle degradation or loss, such as forkhead box protein O3 (FOXO3), myostatin, muscle RING finger protein-1 (MuRF-1), and atrogin-1, were also significantly reduced by treatment with green tea extract with a high EC content in aged mice [21]. Additionally, treatment of antioxidant-rich plant extracts resulted in increased levels of the muscle growth and production factors p70 S6 kinase (pS6K) levels and mammalian target of rapamycin (mTOR), along with the levels of follistatin, which inhibits myostatin [41,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The use of tannase-treated green tea extract containing a high content of EC and GA has been reported to improve skeletal muscle recovery [20,21]. However, whether such beneficial effects occur in humans without added exercise is unknown.…”
Section: Introductionmentioning
confidence: 99%